2014
DOI: 10.2106/jbjs.m.00521
|View full text |Cite
|
Sign up to set email alerts
|

Does Anterior Laxity of the Uninjured Knee Influence Clinical Outcomes of ACL Reconstruction?

Abstract: Greater anterior laxity of the uninjured knee was associated with poorer stability and functional outcomes after ACL reconstruction. Excessive anterior laxity of the uninjured knee thus appears to represent a risk factor for inferior outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Furthermore, they have greater increase in anterior and rotational knee laxity with exercise and fatigue [47•, 48]. Even though the influence of physiological knee laxity on knee function has not been clearly established, several studies suggest it could influence the outcome of ACL reconstructions [49][50][51]. After ACL reconstruction with a bonepatellar-tendon-bone graft (BPTB), patients with an increased physiological laxity have lower Lysholm [50,51] and IKDC subjective [49][50][51] scores.…”
Section: Physiological Laxity Knee Function and Injuriesmentioning
confidence: 99%
“…Furthermore, they have greater increase in anterior and rotational knee laxity with exercise and fatigue [47•, 48]. Even though the influence of physiological knee laxity on knee function has not been clearly established, several studies suggest it could influence the outcome of ACL reconstructions [49][50][51]. After ACL reconstruction with a bonepatellar-tendon-bone graft (BPTB), patients with an increased physiological laxity have lower Lysholm [50,51] and IKDC subjective [49][50][51] scores.…”
Section: Physiological Laxity Knee Function and Injuriesmentioning
confidence: 99%
“…The group with anterior laxity of >7.5 mm in the uninjured knee had poorer functional scores and higher sideto-side laxity measurements compared with patients with £7.5 mm of laxity 26 .…”
Section: Risk Factors For Acl Outcomesmentioning
confidence: 80%
“…Earlier investigators have reported excessive joint laxity as a negative prognostic factor in ligament reconstruction surgery in the knee joint. 10,11,15 Likewise, excessive joint laxity was related to a high recurrence rate after arthroscopic Bankart repair in the setting of moderate to severe glenoid defects. 12 We supposed that excessive joint laxity would negatively affect shoulder stability.…”
Section: Discussionmentioning
confidence: 99%